Response to treatment and adverse events associated with use of recombinant activated factor VII in children: a retrospective cohort study. (February 2017) - Cooper, James D.; Ritchey, Arthur K.
Background: Recombinant activated factor VII (rFVIIa) is United States (US) Food and Drug Administration (FDA)-approved for patients with hemophilia with inhibitors or congenital factor VII deficiency. Initial reports of off-label use highlighted its efficacy, though newer reports have not repeated these findings. In both types of publication, though, secondary thromboses have been seen in adult patients. The data in children are less clear. Methods: This study analyzed all rFVIIa use at a large children's hospital for characteristics and outcomes. Recipients of rFVIIa were identified retrospectively via the electronic medical record. Data on patient diagnosis, lab data, other treatments, adverse events, and outcomes were collected. Results: Over 33 months, 66 patient episodes were treated with a total of 606 doses (median = 2). The most common indication (36.4%) was gastrointestinal bleeding (24/66 patients). Only one patient received a dose for an approved labeled indication. For control of bleeding, 33.3% of courses were unsuccessful (19/57). Bleeding from multiple sites was associated with treatment failure. In 16.7% of patients (11/66), unexpected adverse thromboses developed within 1 week of completing a course of rFVIIa. Thromboses in both intra- and extra-corporeal sites were included if they compromised patient care. Conclusions: In the majority of cases reviewed, rFVIIa was successful in stopping or slowing serious bleeding episodes. It was least effective when a patient had diffuse bleeding at the time of administration. The thrombosis rate of 16.7% was higher than expected, though causality cannot be declared. Further investigation is needed to determine the risk–benefit ratio in children.